Developing a web-based visualization tool for solar energy awareness in Malaysia / Naufal Aniq Khairol Amali ... [et al.] - Khairol Amali, Naufal Aniq; Yahya, Norziana; Md Taib, Mohd Azahani; Jennis, Gloria Tan; Mohd Yusof, Ernie Mazuin (UiTM Cawangan Perlis, 2024)
The aim of this paper is to develop an informative website to address the lack of accessible information and awareness about solar energy usage in Malaysia. The system aims to equip users with knowledge, awareness, and information about solar energy. Additionally, the website incorporates a data visualization feature that demonstrates Malaysia's electrical consumption, enabling users to observe the potential cost savings of utilizing solar energy. The project has three objectives, which are to obtain system requirements for displaying information on solar energy usage in Malaysia, design a data visualization to evaluate Malaysia's suitability for solar energy, and develop an informative website that allows users to explore solar energy data visualization related to Malaysia. The informative website development utilized the Waterfall Model, which progresses through the phases of requirements analysis, system design, and system testing. User Acceptance Testing was conducted to determine the informative website's perceived usability and perceived user satisfaction. The test results indicate that the informative website is a useful tool for allowing users to explore solar energy data visualization related to Malaysia.